2022
DOI: 10.1021/acsomega.2c02834
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Borehole Size on Gas Extraction Borehole Strength and Failure Mode

Abstract: In the coal mine industry, the instability failure of an extraction borehole is one of the main factors leading to the decrease in gas extraction rate. The study on borehole strength and failure mode with different sizes can provide a theoretical basis for the optimization and selection of a gas extraction borehole. In this paper, biaxial loading tests are carried out on similar coal specimens, and the prediction model of borehole strength is proposed and verified. At the same time, numerical simulation of sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…40, 41, and 42). This agrees with the generally observed behavior in borehole failure tests and numerical simulations (Gao and Ren, 2022;Meier et al 2013). The plastic extent around the borehole also increases as the borehole size increases.…”
Section: Effect Of Wellbore Radiussupporting
confidence: 91%
See 1 more Smart Citation
“…40, 41, and 42). This agrees with the generally observed behavior in borehole failure tests and numerical simulations (Gao and Ren, 2022;Meier et al 2013). The plastic extent around the borehole also increases as the borehole size increases.…”
Section: Effect Of Wellbore Radiussupporting
confidence: 91%
“…) + 𝜎 ത 0 ................................................................................................................................. (20). …”
mentioning
confidence: 99%
“…Zhai et al (2015) observed that a circular borehole in an on-site coal seam became elliptical after redistributing in situ stresses. Gao and Ren. (2022) found that circular boreholes deform into elliptical boreholes due to stress exertion in hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, disasters such as coal and gas outburst are likely to occur (Huang et al, 2019;Hao et al, 2021;Bao et al, 2022). Gas extraction is an important technical method to develop and utilize gas resources and prevent gas disasters in coal mines (Yu et al, 2015;Zhang et al, 2022a;Bi et al, 2022;Zhang et al, 2022b;Gao and Ren, 2022). However, under the influence of the excavation and mining of the roadway and borehole, the coal layer could be damaged by different degrees of deformation, so there are a large number of fractures and leakage channels around the extraction borehole Wang et al, 2021;Li et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%